Menjaga Warisan Dongdang Sebagai Jejak Budaya untuk Generasi Mendatang - Yusi Srihartini; Ernawati; Ika Kartika; Chaira Saidah; Ahmadi Usman; Dede Oop Isofah; Mutiara Srikandi; Farij Makarim; Alwi Dahlan; Tubagus Ahmad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The preservation of cultural heritage is the duty and responsibility of all components of society, because the identity of a region can be seen from the culture owned by the region concerned. This article was made according to the experience during the Real Work Lecture in Ciasmara Village through a complete and in-depth description of the sustainable heritage of Dongdang cultural traditions. The method used is Asset-Based Community Development (ABCD). Data were collected through observation and interviews. The results of the study show: Dongdang cultural heritage is a tradition that must be maintained, protected, developed, and preserved and utilized for human welfare. The main priority of tradition development is to build its people, especially the empowerment of local communities and the preservation of cultural heritage as a community resource. The synergy between the welfare of the local community, and the preservation of past heritage is fulfilled, it means that the development of a sustainable dongdang ciasmara tradition can be realized.